Effectiveness of Feedback Strategies in Terms of Accuracy of Peer Assessment - Tiwari, Kavita (INDIAN EDUCATIONAL REVIEW, 2016)
The present research attempted to find out whether the accuracy of peer assessment of achievement can be improved by the use of various feedback strategies. This study was experimental in nature which concentrated on studying the effectiveness of feedback strategies in terms of accuracy of peer assessment of achievement and factors influencing it. The achievement scores of peer assessment were obtained with the help of Achievement test developed by the investigator. The tests used for measuring Intelligence were J.C. Raven’s Standard Progressive Matrices and Raven’s Advanced Progressive Matrices. Self-concept of student-teachers was assessed with the help of Self-Concept Inventory developed by Deo. It is known as Self Concept List (SCL). Two types of treatment were given. For Experimental Group-I Teacher Feedback and for Experimental Group-II Peer Feedback was used as treatment. No treatment was provided to the Control group. Accuracy of Peer Assessment of Achievement of student-teachers was found to be significantly affected by feedback strategy.